Creating Good Administration by Persuasion: A Case Study of the Recommendations of the Committee of Ministers of the Council of Europe - Agnė Andrijauskaitė (Central European Public Administration Review)
This contextual paper tackles a rather under-researched topic of Council of Europe’s possible impact on national administrative law. It seeks to examine how one of its instruments – Recommendations of the Committee of Ministers of the Council of Europe – can influence national standards of administrative law and provide a systematic assessment of the diverse functions and manifestations such instruments might have in a national legal order. For these purposes, the constitutional basis of these recommendations and their main features are examined followed by a subsequent analysis of the perceived importance and various functions and implications they might have in the chosen national legal system. This paper concludes that the scope of the functions and implications these instruments are capable of having to national administrative law is wide, yet it is not without limitations.